"Politics in tne developing world / edited by Peter Burnell, Vicky Randall and Lise Rakner" - "Burnell, Peter.(ed.)" (New York, 2008)
An impressive line-up of international contributors provides a comprehensive and accessible introduction to politics in the developing world. The first four parts explore the theoretical approaches, the changing nature and role of the state, and the major policy issues that confront all developing countries. The final parts set out a diverse range of country case studies, representing all the main geographical regions. These country case studies illustrate the themes introduced in the thematic chapters and highlight the developing world as a place of diversity and rapid transformations. Readers are provided with the tools to appreciate the perspectives of developing countries.
Keywords: Politics-Developing countries